Pengabdian kepada Masyarakat Strategi Memasuki Pasar Global untuk Meningkatkan Pendapatan Keuangan Mse Tenun Ikat di Jepara Kudus - Masno Marjohan; Sri Retnaning Sampurnaningsih; Pranoto Pranoto (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
Financial statements are information related to finance in a company where it can be used to analyze the company's condition and assess the company's capacity in a separate period and increase healthy financial flow. In the accounting cycle for one period, it can be ensured monthly, semester or for a period of one year. Community Service Activity with the title Entering Tthe Global market Strategy to Encrease Financial Sttream of Weaving Ikat MSEs in Jepara Kudus. The purpose of Community Service is to provide briefings on how to enter the global market to increase financial flows in micro and small fish weaving businesses in Jepara. The activity method used was presentation and question and answer to the PKM participants. It is hoped that the results of this activity are that the participants can understand how the strategy to enter the global market such as exports which is ultimately expected to increase the income and welfare of micro and small businesses in Jepara in particular. The results of this Community Service are expected to achieve a global market strategy and to increase financial flows for MSMEs.